Modelling Sustainable Mathematics Teaching and Learning in Nepal - Poudel, Bishnu Prasad (Journal of Interdisciplinary Studies, 2026)
Sustainable mathematics education is crucial in the development of the sustained mathematical knowledge, confidence and understanding in real life contexts of students. However, mathematics learning in Nepal continues to be hindered by mathematics anxiety, having insufficient teaching resources, teacher-dominated teaching style, and an examination-driven assessment system. A few studies have looked at these aspects separately, but few studies have taken into account cognitive, affective, pedagogical and contextual aspects together in a comprehensive framework for sustainable mathematics learning. This study aims to overcome this limitation by creating the model for sustainable mathematics teaching and learning in Nepali secondary school. The convergent, mixed methods approach was used. 102 secondary level students from public and private schools were selected in Nepal for quantitative and qualitative data collection. The data were collected by using structured questionnaires, open-ended responses, interviews and classroom observations. Descriptive statistics, correlation, and multiple regression analysis were used to analyze quantitative data, and thematic analysis was used to analyze qualitative data. The results indicated that there were negative relationships between mathematics anxiety and students’ motivation, confidence, and involvement in mathematics learning. On the other hand, student-centered teaching method and learning environment and good use of contextual resources were positively related to sustainable mathematics learning. From the regression analysis, it was found that the teaching-learning practices, learning resources, and student motivation were significant predictors of sustainable mathematics learning. Qualitative results also showed that examination pressure, insufficient teaching materials, and traditional teaching pedagogies affected students’ learning experience. These results provide the basis for the development of a sustainable mathematics education model consisting of four inter woven dimensions, namely Pedagogical Empowerment, Affective Support, Contextual Resource Utilization, and Systemic Feedback Loops. Based on the results, the study suggests some shifts in pedagogical practices that are necessary to promote sustainable mathematics learning in the context of Nepal, which include shift from examining-centred and teacher-led approaches to learner centred approaches in mathematics teaching, continuous professional development of teachers, contextualization of resources, and change in assessment from summative to formative assessment practices.